The Role of Microsatellite Instability in Positive Margin Gastric Cancer Patients. (April 2018) - Polom, Karol; Marrelli, Daniele; Smyth, Elizabeth C.; Voglino, Costantino; Roviello, Giandomenico; Pascale, Valeria; Varas, Julian; Vindigni, Carla; Roviello, Franco
Purpose . A positive resection margin (RM+) is acknowledged as a poor prognostic factor after gastrectomy. Microsatellite instability (MSI-H) gastric cancer has been identified as a subgroup of gastric cancer that may be associated with an improved prognosis. The aim of the study was an analysis of MSI status on patients with margin involvement after gastrectomy and examination of the association between MSI, margin status, and survival outcomes. Methods . From a large prospectively annotated surgical database we collected clinicopathological and survival data on patients who had undergone a potentially curative resection for gastric cancer. MSI status was assessed using a standard 5-marker quasi-monomorphic mononucleotide repeat panel. Patients who were R+ and either microsatellite stable (MSS) or MSI-H were identified and clinicopathological characteristics and disease specific survival was compared. Results . Three hundred and eighty-six patients were identified; 102 (26.4%) cancers were MSI-H. The proportion of R+ resections was not significantly different in MSS and MSI-H groups. For MSS patients 3-, 5-, and 10-year disease-specific survival rates were 9.1%, 0%, and 0%, respectively; for patients with MSI-H R+ tumors these were 38.5%, 30.8%, and 15.4%, respectively. In Cox analysis MSI-H, female gender, and T ≥3 were significantly associated with survival. Conclusions . Patients with MSI-H gastric cancer may have long-term survival despite R+ margin status. The molecular division of gastric cancer may be an important step in identifying possible tailored surgical treatments corresponding to clinical and pathological factors.